Lattice distortion in Cu-based dilute alloys: A first-principles study by the KKR Green-function method - N. Papanikolaou; R. Zeller; P.H. Dederichs; N. Stefanou (Physical Review B, 1997)
The full-potential Korringa-Kohn-Rostoker Green function method is extended to treat the lattice distortion in the vicinity of a point defect. The method is applied to predict the atomic positions in the neighborhood of d and sp substitutional impurities in Cu. Both the total energy and the Hellmann-Feynman force are used for the calculation of the ground-state configuration, while the semicore states of the impurities are treated as valence states. Our results for the atomic displacements are in very good agreement with the experimental data from extended x-ray-absorption fine-structure and lattice-parameter measurements.